Micromagnetic and morphological characterization of heteropolymer human ferritin cores - Longo, Thomas; Kim, Steve; Srivastava, Ayush K; Hurley, Lauren; Ji, Kaixuan; Viescas, Arthur J; Flint, Nicholas; Foucher, Alexandre C; Yates, Douglas; Stach, Eric A; Bou-Abdallah, Fadi; Papaefthymiou, Georgia C (Nanoscale advances, 2022)
The physical properties of in vitro iron-reconstituted and genetically engineered human heteropolymer ferritins were investigated. High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM), electron energy-loss spectroscopy (EELS), and 57 Fe Mössbauer spectroscopy were employed to ascertain (1) the microstructural, electronic, and micromagnetic properties of the nanosized iron cores, and (2) the effect of the H and L ferritin subunit ratios on these properties. Mössbauer spectroscopic signatures indicate that all iron within the core is in the high spin ferric state. Variable temperature Mössbauer spectroscopy for H-rich (H 21 /L 3 ) and L-rich (H 2 /L 22 ) ferritins reconstituted at 1000 57 Fe/protein indicates superparamagnetic behavior with blocking temperatures of 19 K and 28 K, while HAADF-STEM measurements give average core diameters of (3.7 ± 0.6) nm and (5.9 ± 1.0) nm, respectively. Most significantly, H-rich proteins reveal elongated, dumbbell, and crescent-shaped cores, while L-rich proteins present spherical cores, pointing to a correlation between core shape and protein shell composition. Assuming an attempt time for spin reversal of τ 0 = 10 −11 s, the Néel-Brown formula for spin-relaxation time predicts effective magnetic anisotropy energy densities of 6.83 × 10 4 J m −3 and 2.75 × 10 4 J m −3 for H-rich and L-rich proteins, respectively, due to differences in surface and shape contributions to magnetic anisotropy in the two heteropolymers. The observed differences in shape, size, and effective magnetic anisotropies of the derived biomineral cores are discussed in terms of the iron nucleation sites within the interior surface of the heteropolymer shells for H-rich and L-rich proteins. Overall, our results imply that site-directed nucleation and core growth within the protein cavity play a determinant role in the resulting core morphology. Our findings have relevance to iron biomineralization processes in nature and the growth of designer's magnetic nanoparticles within recombinant apoferritin nano-templates for nanotechnology. The physical properties of in vitro iron-reconstituted and genetically engineered human heteropolymer ferritins were investigated.